STUDI PENURUNAN WARNA REAKTIF PADA AIR LIMBAH TEKSTIL DENGAN PROSES FOTOKIMIA UV/H2O2/TiO2 - Meria Fifiani (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
Photochemistry, as well as H2O2 as oxidator and TiO2 as catalyst in the photochemical process, has been widely used as one of alternatives in the wastewater treatment process. During the photocemical process, hydroxyl radical is formed, and it reduces organics substances present in the wastewater, such as textile colouring. The research showed that the usage of UV/H2O2, with 0,05% dosage of H2O2, gave the maximum colouring removal of 99,2%. The combination of UV/TiO2, with 1% dosage of TiO2, gave the maximum colouring removal of 27,8%. As well as these, the combination of UV/H2O2/TiO2 with ratio of H2O2:TiO2 = 1:0, gave the maximum removal of 99,2%.